How histopathologic changes in pediatric nonalcoholic fatty liver disease influence in vivo liver stiffness. (15th March 2021) - Hudert, Christian A.; Tzschätzsch, Heiko; Rudolph, Birgit; Loddenkemper, Christoph; Holzhütter, Hermann-Georg; Kalveram, Laura; Wiegand, Susanna; Braun, Jürgen; Sack, Ingolf; Guo, Jing
Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in children and adolescents. About 30% of patients with NAFLD progress to the more severe condition of nonalcoholic steatohepatitis (NASH), which is typically diagnosed using liver biopsy. Liver stiffness (LS) quantified by elastography is a promising imaging marker for the noninvasive assessment of NAFLD and NASH in pediatric patients. However, the link between LS and specific histopathologic features used for clinical staging of NAFLD is not well defined. Furthermore, LS data reported in the literature can vary greatly due to the use of different measurement techniques. Uniquely, time-harmonic elastography (THE) based on ultrasound and magnetic resonance elastography (MRE) use the same mechanical stimulation, allowing us to compare LS in biopsy-proven NAFLD previously determined by THE and MRE in 67 and 50 adolescents, respectively. In the present work, we analyzed the influence of seven distinct histopathologic features on LS, including septal infiltration, bridging fibrosis, pericellular fibrosis, hepatocellular ballooning, portal inflammation, lobular inflammation, and steatosis. LS was highly correlated with periportal and lobular fibrosis as well as hepatocellular ballooning while no independent association was found for inflammation and steatosis. Based on this analysis, we propose a composite elastography score (CES) which includes the four key histopathologic features identified as mechanically relevant. Interestingly, CES-relevant histopathologic features were associated with zonal distribution patterns of pediatric NAFLD. Mechano-structural changes associated with NAFLD progression can be histopathologically staged using the CES, which is easily determined noninvasively based on LS measured by time-harmonic elastography. Graphical abstract: Image, graphical abstract